EMPLOYEE PERFORMANCE BASED ON COMPETENCE, WORK DISCIPLINE, AND ENVIRONMENT AT PT. ANUGRAH BERSAMA SEJAHTERA DEPOK - Ading Sunarto; Mohamad Duddy Dinantara; Edy Krisyanto (International Journal of Economy, Education and Entrepreneurship, 2023)
This study aims to determine the effect of competence on employee performance at PT. Anugrah Bersama Sejahtera Depok, to determine the effect of Work Discipline on employee performance at PT. Anugrah Bersama Sejahtera Depok, to determine the effect of the work environment on employee performance at PT. Anugrah Bersama Sejahtera Depok and to determine the influence of competence, work discipline, and work environment together at PT. Anugrah Together Prosperous Depok. The population and sample in this study are employees of PT. Anugrah Bersama Sejahtera Depok with a total sample of 128 respondents. This research is quantitative. Furthermore, the sampling technique is nonprobability sampling, taken from saturated sampling (census). Data analysis techniques used include validity test, reliability test, normality test, multi-correlation test, heteroscedasticity test, linear regression, coefficient of determination, and significant test (t-test and F test). Competence has a positive and significant effect on employee performance at PT. Anugrah Together Prosperous Depok. This can be seen from the value of tcount > ttable (8.971 > 1.979) and t significance <0.05 (0.000 <0.05). The simple regression model obtained is Y = 17.176 + 0.612X1. Competence has a contribution (R2) of 39% to employee performance at PT. Anugrah Together Prosperous Depok. Work Discipline has a positive and significant effect on employee performance at PT. Anugrah Together Prosperous Depok. This can be seen from the value of tcount > ttable (9.354 > 1.979) and t significance <0.05 (0.000 <0.05). Work discipline has a contribution (R2) of 41% to employee performance at PT. Anugrah Together Prosperous Depok. The simple regression model obtained is Y = 20.244 + 0.666X2. The work environment positively and significantly affects employee performance at PT. Anugrah Together Prosperous Depok. This can be seen from the value of tcount > ttable (8.754 > 1.979) and t significance <0.05 (0.000 <0.05). The simple regression model obtained is Y = 19.918 + 0.678X3. The work environment has a contribution (R2) of 37.8% to the performance of employees at PT. Anugrah Together Prosperous Depok. Competence, work discipline, and work environment have a positive and significant effect on the performance of employees at PT. Anugrah Together Prosperous Depok. It can be seen from the value of Fcount > Ftable (71.041 > 2.677) and F significance F <0.05 (0.000 <0.05). Competence, work discipline, and work environment together have a contribution (R2) of 62.3% to the performance of employees at PT. Anugrah Bersama Sejahtera Depok, the remaining 37.7% is influenced by other variables not examined. The multiple regression model obtained is Y = 2.984 + 0.341X1 + 0.405X2+ 0.297 X3